Penerapan Tata Kelola Badan Usaha Milik Desa dalam Mewujudkan Sustainable Development Goals Desa - Elfrida Yuliana; Natasia Alinsari (Politeknik Ganesha Medan, 2022)
The implementation of village SDGs aims to support the achievement of the SDGs nationally. The purpose of the village SDGs is an effort to realize equitable village economic growth. Realized equity and village economic growth by using village funds to establish Village-Owned Enterprises (BUMDes). The importance of BUMDes management is based on governance principles to achieve equity and village economic growth through BUMDes. BUMDes governance principles consist of cooperative, participatory, emancipatory, transparent, accountable, and sustainable. The research aims to describe how the implementation of BUMDes Estu Mukti governance in realizing the village SDGs in Bejalen Village. The research method used is a qualitative descriptive approach using primary and secondary data. The data analysis technique used the triangulation technique, consisting of data reduction, data display, and conclusion drawing. This research indicates that the principles of governance in BUMDes Estu Mukti are applied correctly. The business units managed by BUMDes Estu Mukti are very supportive of the community's economy so that there is an increase in the village economy and social welfare. Based on the research results, the implementation of governance principles in BUMDes Estu Mukti is appropriate and consistent with the effect that helps the weal of the society and the village economy increase. This research concludes that Bejalen Village has realized the village SDGs program, namely the equitable distribution of village economic growth through BUMDes Estu Mukti.